Fiber vs. vectoring: Limiting technology choices in broadband expansion - Niklas Fourberg; Alex Korff (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
The upgrade of legacy infrastructure is a challenging undertaking in general. The underlying issues are especially prominent for telecommunications networks outside of urban areas. Using German micro-level data, we identify the structural determinants for fiber optics deployment and its extent. We also measure the role of technology competition from the existing infrastructures, VDSL-Vectoring and TV-Cable. In this setting and exploiting a natural experiment, a technologically restrictive policy as proposed by the European Commission is found to be ineffective in promoting fiber deployment. Policy interventions in the form of subsidies targeted at specific local infrastructure projects, however, raise the likelihood of fiber deployment by a substantial margin. A targeted, proactive policy approach is therefore needed to overcome structural and geographical disadvantages.
Keywords: D22; L52; L86; L96; O18; 330; Fiber expansion; Technology competition; Technology regulation; Subsidies; Regional Infrastructure